1999
DOI: 10.1161/01.str.30.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Incidence and Case Fatality in Southern Greece

Abstract: Background and Purpose-For Greece, information on incidence of stroke and distribution of type of stroke has not been reported. We determined the incidence of first-ever stroke in men and women, the incidence of stroke by type, and the associated case fatality. Methods-A population-based registry was established in the Arcadia province, located in eastern central Peloponessos, in the southern part of Greece. Between November 1, 1993, and October 31, 1995, all subjects with a first-ever stroke were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
114
8
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 37 publications
18
114
8
5
Order By: Relevance
“…These survival factors are a little higher than those reported by Morrison et al (1997) for CHD based on a community study in Glasgow, and by Vemmos et al (1999) for stroke based on a study carried out in southern Greece. This is discussed in detail in Wekwete (2002, Section 3.1.3).…”
Section: Preliminariescontrasting
confidence: 62%
“…These survival factors are a little higher than those reported by Morrison et al (1997) for CHD based on a community study in Glasgow, and by Vemmos et al (1999) for stroke based on a study carried out in southern Greece. This is discussed in detail in Wekwete (2002, Section 3.1.3).…”
Section: Preliminariescontrasting
confidence: 62%
“…The WHO incidence rates were compared with ÔidealÕ stroke studies and the rates were largely within the range of rates from studies. It should be noted that WHO estimates for Portugal and Greece were markedly higher than reported [15,40]. It remains unclear if routine mortality statistics from these countries over-report the number of stroke deaths, or if the studies have registered stroke events in subpopulations with low stroke rates, and is a good example of the need to increase stroke data collection in countries.…”
Section: Stroke Incidence and Prevalence In Europementioning
confidence: 98%
“…[7][8][9][10][11][12][13][14][15][16] Previous studies in China, Hong Kong, Taiwan, and Japan generally found that 23% to 52.2% of strokes were hemorrhagic, [3][4][5][6][21][22][23][24][25] in contrast to only 9% to 18% in whites. [7][8][9][10][11][12][13][14][15][16] In the present study, 29.6% of stroke cases overall in 2000 were hemorrhagic in Chinese populations, which supported the above idea that an ethnic difference existed between Eastern and Western populations. Further analysis showed that the proportion of hemorrhagic stroke among all strokes varied from 19.4% to 42.2% in the 10 populations, although all the study populations came from the same race, Han people.…”
Section: Stroke Subtypes In Chinese Populations Compared With Westernmentioning
confidence: 99%
“…Most previous studies suggested that at least 30% of strokes in China were hemorrhagic strokes 4,5 ; some studies even reported that Ͼ50% of strokes were hemorrhagic, 6 which was significantly different from the findings in whites. [7][8][9][10][11][12][13][14][15][16] However, most of these previous studies either limited the study population to a confined area or based the diagnosis criteria mainly on clinical presentations. In recent years, CT scan rate of stroke patients has increased rapidly, which makes it possible to examine the stroke subtypes more accurately in Chinese populations.…”
mentioning
confidence: 99%